Kontekstualisasi Hadis ‘Berkata Baik Atau Diam’ Sebagai Larangan Hate Speech di Media Sosial:: Aplikasi Double Movement Fazlur Rahman - Lestari, Sri Hariyati; HS, Muhammad Alwi (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2020)
This article aims to contextualize the hadith of Al-Bukhari's transmission number 5.559 about 'speaking the good or remain silent' through the Double Movement theory from Fazlu Rahman, which will then become the basis for a ban on the phenomenon of hate speech on social media. This departs from the reality of hate speech that is increasingly rampant, even though the act has been banned in the Circular Chief of Police number SE / 06 / X / 2005. After analyzing and analyzing the history of Al-Bukhari number 5559, this article concludes that the hadith is a response to the bad behavior experienced by Muhammad bin Abdullah bin Salam from his neighbor, one of which is mentioned in the hadith is not saying good, as an antonym of the word saying good. Behavior of not saying good here is also in line with the phenomenon of hate speech, especially entering the media era. The moral ideal of this tradition is as a command to say good, if it is unable or unwilling, it is better to be quiet, rather than doing hate speech. As for the threat of hate speech,, as the moral ideal of the hadith here, is not included as those who believe because they are not good or silent, but instead do hate speech.